Occurrence of Acrylamide in Italian Baked Products and Dietary Exposure Assessment - Francesco Esposito; Salvatore Velotto; Teresa Rea; Tommaso Stasi; Teresa Cirillo (Molecules, 2020)
Acrylamide (AA) is a neo-formed toxic compound that develops in foods during cooking at temperatures above 120 °C. AA shows in vivo neurotoxic and carcinogenic effects, and it is potentially carcinogenic for humans. Its occurrence is common in baked food, such as bread and similar products. This study set out to analyze bread and sweets from the Italian market to evaluate the effects of the benchmark thresholds set by EU Regulation 2017/2158 and to ascertain the exposure of the Italian population to AA, across three age groups, through the consumption of baked products, according to the margin of exposure (MOE) approach. Two hundred samples were tested, and the content of AA ranged from 31 to 454 µg/kg for bread and products thereof and from 204 to 400 µg/kg for the sweets category. The exposure data did not show any neurotoxic health concern, whereas the MOE related to the carcinogenic endpoint is well below the minimum safety value of 10,000.